Effect of modified surgical conditions on the peripapillary microvasculature and RNFL in patients receiving vitrectomy: an OCTA study - Ting Pan; Cunxin Bian; Yuan Fang; Jingfan Wang; Yidan Xu; Ping Xie; Zizhong Hu (BMC Ophthalmology)
Abstract Purpose Pars plana vitrectomy (PPV) is an effective treatment of vitreoretinal diseases, while some studies reported visual field defects after surgery. The aim of this study was to evaluate the protective effects of modified vitrectomy surgical conditions on peripapillary microvasculature and retinal nerve fiber layer (RNFL) changes using optical coherence tomography angiography (OCTA). Methods This was a retrospectively study and the medical records of 37 patients diagnosed with iERM or iMH underwent PPV with ILM peeling were retrospectively reviewed. Patients were divided into two groups according to different surgical conditions. Peripapillary OCTA images were acquired at pre-operation, 1 week, 1 month, and 3 months post-operation. Best corrected visual acuity (BCVA) was recorded. Intraocular pressure (IOP) was measured with Goldman applanation tonometer. Fisher’s exact test, the Mann-Whitney U test, t test, and repeated-measures analysis of variance (RM-ANOVA) were used to analyze our data. Results The primary metrics found was the radial peripapillary capillary (RPC) small vessel density. The RPC in the protective group was significantly increased compared with the control group after surgery. At 3 months after vitrectomy, the mean and superior quadrant peripapillary RNFL thickness in the protective group was significantly higher than those in the control group. BCVA was improved in both groups at 3 months after surgery. BCVA and IOP did not differ significantly between these two groups pre- and post-operation. Conclusion Vitrectomy with ILM peeling may cause peripapillary microvascular and RNFL damage. The application of a modified surgical conditions may do some help in the recovery of peripapillary blood flow and peripapillary RNFL thickness.